An investigation into the implementation of group work, as a method of social work intervention, in health settings in South Africa - Caires, Juliet Margarita (Rhodes University, Faculty of Humanities, Department of Social Work, 1999)
This research aims to discover whether social workers employed in health settings in South Africa use group work as a method of intervention with patients. It attempts to explore in which hospitals (or particular patient populations) group work is considered possible, and to discover to what extent social workers in health settings consider group work to be beneficial to patients. It also attempts to discover some of the potential difficulties experienced in initiating group work in medical settings. An effort is also made to establish, from social workers active and experienced in the field of medical social work,what place group work might have in the broader context of health services in the future. Data was obtained through the use of mailed questionnaires, which were sent to 186 health settings, across South Africa. These settings were chosen according to the following priorities: i) those known to have social workers ii) services offered (e.g. oncology, psychotherapy) iii) size of the setting iv) geographical location (both urban and rural in all nine provinces). The sample included general public and private hospitals, psychiatric hospitals (both public and private), mining hospitals and other health settings such as old age homes and facilities for the mentally retarded and for alcohol and drug rehabilitation (accompanied by a medical facility). Responses were received from 90 health settings, with 64 of these being completed questionnaires. The majority of responses came from public hospitals, and the least from the mining hospital category. Findings of this study indicate that group work is used by 50% of the health settings in South Africa. Groups are most often therapeutic or educational in nature, are run on average once a week for an hour, and are usually of open membership. Group work is not used in some health settings, most commonly due to insufficient time (on the part of the social worker). From the findings, it seems that many more social workers would like to run groups for patients than they do presently. The benefits of group work are acknowledged by the majority of this study's sample of social workers, and if solutions could be found to problems such as heavy caseloads and insufficient time, more social workers would choose to use group work than are doing so currently. Group work is considered to be a feasible method, both in the hospitals and at primary health care level. With South Africa's growing emphasis on primary health care, and the proposed inclusion (by the Department of Health) of social work services at this level, it is important that social workers find a way in which to meet the needs of patients at both levels. With group work, this may be possible.
Keywords: Social group work; Community health services -- South Africa; Medical care -- South Africa